Lyme borreliosis--analysis of the trends in Slovakia, 1999-2008 - Svihrova, Viera; Hudeckova, Henrieta; Jesenak, Milos; Schwarzova, Katarina; Kostanova, Zina; Ciznar, Ivan (Folia microbiologica, 2011)
Lyme borreliosis (LB) presents as one of the most frequent tick-borne diseases in Europe with more than 85,000 reported cases every year. The transport of this disease on humans is by tick species of the genus Ixodes. In our work, we aimed to perform a retrospective analysis of the incidence and seasonality of Lyme borreliosis during the period 1999-2008 in Slovakia. For our analysis, we used all the relevant data about the patients with Lyme borreliosis reported in the Epidemiological Informative System of Communicable Diseases in Slovakia during the decade of 1999-2008. During the observed period, there were 7,349 reported cases of LB in Slovakia. Whereas the incidence of early localized infection did not change during the observed period, there was a significant increase in the incidence of early disseminated infection and late persistent infection of LB. Seventy per cent of all patients was infected by tick bite. LB was more frequently reported in females than in males (56.1% vs. 43.9%; p < 0.05), and the most involved age group was the productive age (15-64 years). The incidence of disseminated infection and persistent infection was rising with increasing age. Regarding the seasonality of LB, we found the highest incidence during the summer months. Comparing the situation of LB in 1999 and 2008, significant increase in the number of reported cases was in April and June and from September to November (p < 0.05). Our epidemiological analysis confirmed that Lyme borreliosis requires increased attention due to its increasing incidence.
Keywords: lymeská nemoc; dospělí; Animals; Borrelia; Female; Tick-Borne Diseases; klíště; Adult; ženské pohlaví; Adolescent; Slovakia; lidé; nemoci přenášené klíšťaty; Incidence; Male; incidence; Lyme Disease; lidé středního věku; Slovenská republika; zvířata; mužské pohlaví; Middle Aged; mladiství; Ixodes; Humans